Risk factors associated with the incidence of Arteriovenous (AV) shunt stenosis in Chronic Kidney Disease (CKD) patients on hemodialysis - Gunawan, Atma; Rifai, Achmad; Kurnianingsih, Novi; Haryanto, Ahmad Farid (Journal of Indonesia Vascular Access, 2025)
Background: Arteriovenous (AV) shunt stenosis is a significant complication in chronic kidney disease (CKD) patients undergoing hemodialysis with AV shunt access. The risk factors associated with this event are still not fully understood. This study aims to identify factors associated with the incidence of AV shunt stenosis in CKD patients undergoing dialysis. Methods: A cross-sectional study was conducted involving 236 patients undergoing hemodialysis at Dr. Saiful Anwar General Hospital, Malang. Risk factors analyzed included age, gender, diabetes mellitus, hypertension, obesity, and AV shunt location. Results: Bivariate analysis using the Chi-square test showed significant associations between stenosis and age (p=0.020), gender (p=0.001), diabetes mellitus (p=0.001), and hypertension (p=0.031). However, obesity (p=0.608) and AV shunt location (p=0.552) were not significantly associated. Logistic regression analysis indicated that diabetes mellitus increased the risk of AV shunt stenosis by 2.46 times (95% CI: 1.42-4.26), hypertension by 2.05 times (95% CI: 1.06-3.96), and age above 60 years by 1.93 times (95% CI: 1.10-3.37) Conclusion: Diabetes mellitus, hypertension, advanced age, and smoking are key risk factors for AV shunt stenosis in CKD patients undergoing dialysis